WAYS TO ELIMINATE DEFICIENCIES IN READING AND WRITING AMONG PRIMARY SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2025)
Learning letters for primary school students is the process of being able to write them in the correct order and, above all, acquiring knowledge of reading and writing without deficiencies. In these phases we can see that some students have deficits for various reasons. Addressing these deficiencies requires the collaboration of teachers, parents and students.